Improving Mathematical Problem-Solving Skills through the Problem-Based Learning Model on Financial Literacy Material - Uliana; Napitupulu, Bettisari; Hutabarat, Ida Mariati (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2025)
This study investigates the effectiveness of the Problem Based Learning (PBL) model in enhancing students’ mathematical problem solving skills within the context of financial literacy. The study was motivated by the low level of students’ ability to solve mathematical problems, particularly in applying concepts related to financial literacy. The purpose of this research was to improve students’ problem solving skills by implementing the PBL model as an alternative to conventional teacher centered learning. The study employed a Classroom Action Research (CAR) design conducted with seventh grade students at SMP Al Ihsan Kotaraja, Jayapura City. The research was carried out in two stages consisting of a preliminary phase and one cycle of PBL implementation. The findings indicate that the application of the PBL model led to notable improvements in students’ mathematical problem solving abilities. The results also revealed that students became more engaged, enthusiastic, and independent in the learning process. Teacher activities were observed to be more effective in facilitating student centered learning through the use of contextual problems in financial literacy. In conclusion, the PBL model proved to be an effective instructional approach for strengthening mathematical problem solving skills while simultaneously fostering collaboration, critical thinking, and meaningful learning experiences in financial literacy.